The Repercussions of Integrating Magnetite into Magnetorheological Elastomers to Diminish Vibration - Priyandoko, Gigih (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Vibration damping is a very important part of engineering systems. If vibrations are too strong, they can make things vibrate more, wear out materials, reduce how well things work, and make structures fail too soon. This is especially true for vibrations that are low to medium in frequency. The objective of this study is to examine the impact of magnetite incorporation on the magnetorheological elastomers (MREs) for efficient vibration reduction within the frequency range of 1–100 Hz. MRE samples were fabricated using silicone rubber as the elastomer matrix. Silicone oil was used as a plasticizer. Carbonyl iron particles were used as the magnetorheological phase. Magnetite nanoparticles were added at different weight fractions. The material's morphology and elemental composition were examined using a SEM–EDX. To evaluate storage modulus, loss modulus, and damping factor (tan δ), dynamic rheological characterization was conducted using a Discovery Hybrid Rheometer. The results show that adding magnetite has a big impact on the viscoelastic behavior of MREs, reducing dynamic stiffness and increasing internal energy dissipation. However, the effect varies greatly based on the amount of magnetite added. The compositions that were investigated revealed that MRE with 1% magnetite has the lowest storage modulus, stable loss modulus, and the highest and most consistent tan δ values across the tested frequency range. This demonstrates that it has superior vibration-damping performance compared to other formulations.